ChemInform Abstract: Combination of Ru(II) Complexes and Light: New Frontiers in Cancer Therapy. Issue 25 (5th June 2015) - Mari, Cristina; Pierroz, Vanessa; Ferrari, Stefano; Gasser, Gilles
Abstract: Review: 116 refs.